Phosphorylation-driven conformational switching of the ArnA–ArnB complex involved in archaeal motility regulation - Watad, Mohamed; Korf, Lukas; Steinchen, Wieland; Bezold, Filipp; Vogt, Marian S.; Wang, Po Hsun; Selbach, Leon; Hepp, Sebastian; Gayermann, Luis; van Wolferen, Marleen; Ye, Xing; Albers, Sonja-Verena; et al. (Frontiers in Microbiology, 2026)
ArnA and ArnB serve as regulators within the Sulfolobus archaellum regulatory network by modulating the archaellum components ArlB and ArlX, which are essential for swimming motility. Together, they form a dynamic complex that, depending on nutrient availability, exists in either a loose, unphosphorylated or a tight, phosphorylated state. This transition is directed by phosphorylation via the kinase ArnC. To investigate this transition, we determined the cocrystal structure of the ArnA/ArnB complex, revealing that the zinc finger domain of ArnA interacts with both the β-sandwich and the C-terminal domains of ArnB. HDX data support the phosphorylation-dependent transition from a loose to a tight ArnAB complex driven by sequential phosphorylation of ArnB. This modification exposes the interaction surface of the C-terminal domain of ArnB, which then binds to the forkhead-associated domain of ArnA. Upon starvation of deletion strains of arnA and arnB, a reduction of ArnA was observed in the ΔarnB strain, and a reduction in ArnB levels was seen in the ΔarnA strain. Additionally, several putative transcriptional regulators were affected, suggesting downstream regulatory effects. These results highlight the critical role of the ArnAB complex in regulating the archaellum response to nutrient cues and provide new insights into the complex regulatory network governing archaeal swimming motility.